Minimally invasive mitral valve reconstruction: Is it an "all‐comers" procedure?. Issue 10 (15th November 2021) - Speziale, Giuseppe; Santarpino, Giuseppe; Moscarelli, Marco; Di Bari, Nicola; Fiore, Flavio; Condello, Ignazio; Bartolomucci, Francesco; Bellino, Maria C.; Nasso, Giuseppe
Abstract: Background and Aim of the Study: The debate on the usefulness of the minimally invasive approach in mitral valve surgery is still open. The aim of this study is to describe a single‐center case series of all comers undergoing minimally invasive mitral valve reconstruction. Methods: From 2010 to 2019, all the data recorded in the medical records of 893 consecutive patients undergoing mitral valve reconstruction through a right mini‐thoracotomy were retrospectively collected. All patients were contacted by telephone for remote evaluation and integration of echocardiographic information on surgical results. Results: Mean age was 62.2 ± 14.5; 447 (50%) were female and mean log EuroSCORE was 2.5 ± 2.8%. At a mean follow‐up of 4.1 ± 2.2 years (median 3.9), a total of 24 deaths (2.68%) were recorded. Twenty‐four patients required rehospitalization for cardiac causes, 13 (1.4%) patients had at least moderate mitral insufficiency on follow‐up echocardiography and, of these, seven patients underwent reoperation (0.8%). The cumulative hazard showed that 8.3% of patients experienced at least one event at 5 years. NYHA class improved significantly with 874 patients in NYHA class I, 13 in NYHA class II, 6 in NYHA class III, and 0 in NYHA class IV at last follow‐up ( p < .001 from baseline as reference point). Conclusions: In a high‐volume center, mitral valve surgery using a minimally invasive approach is a feasible treatment option for all‐comers and is associated with excellent results that are maintained at clinical and echocardiographic follow‐up.